Understanding world Christianity : China - Chan, Kim-Kwong, 1958- (Understanding world Christianity series., 2019)
The Understanding World Christianity series is organized geographically, by nation and region. Noted experts, in most cases native to the area of focus, present a balanced history of Christianity and a detailed discussion of the faith as it is lived today. This volume on China is an ideal introduction for anyone who wishes to know how Christianity is lived in the Chinese context.